Poly(ethylene glycol)/Polyvinyl chloride Composite Form-Stable Phase-Change Materials by the Azide-Alkyne Click Reaction - OKTAY, BURCU (WILEY-V C H VERLAG GMBH, 2018)
Thermal energy storage has become a key area in modern technology. Polyethylene glycol (PEG) is known to be an extremely effective solid-liquid phase change material (PCM). For efficient energy storage, alternative liquid-solid PCMs without encapsulation were designed. In particular, a series of PCMs, comprising PEG-stearate and PEG-stearate-Polyvinyl chloride (PVC), were prepared by the azide-alkyne cycloaddition click reaction. The click reactions of azido-PEG, azido-PVC, and alkynyl stearate were carried out. The prepared polymers, PEG-stearate and PEG-stearate-PVC PCMs were characterized by Fourier-transform infrared spectroscopy (FTIR) spectroscopy. The latent heat and thermal stability of PCMs were investigated by Differential Scanning Calorimetry (DSC) and Thermogravimetric analyzer (TGA). DSC results revealed that PCMs exhibit latent heat values ranging from 80 to 104 J/g at -2 and 46 degrees C. In addition, PCMs exhibited high thermal stability with the increase in the content of PVC.
Keywords: azide-alkyne; click chemistry; energy storage; phase change material; polymer composites; THERMAL-ENERGY STORAGE; POLYETHYLENE-GLYCOL; PERFORMANCE; BLENDS